2018
DOI: 10.1080/14767058.2018.1463984
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal cord: impact of umbilical artery Doppler indices on intrapartum and neonatal outcomes: a prospective cohort study

Abstract: In view of these results, it might be concluded that umbilical cord tightness affecting fetal hemodynamics (expressed by changes in umbilical artery Doppler) might be a determinate factor affecting the intrapartum course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For this element, a positive index test result was any nuchal cord suspected antenatally using ultrasound and the reference standard was the presence of a nuchal cord at birth. Results were combined for ultrasound screening at any gestation; four studies [ 7 , 30 32 ] performed screening immediately prior to induction or during labour and in all but two studies all measurements were performed after 36 weeks [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this element, a positive index test result was any nuchal cord suspected antenatally using ultrasound and the reference standard was the presence of a nuchal cord at birth. Results were combined for ultrasound screening at any gestation; four studies [ 7 , 30 32 ] performed screening immediately prior to induction or during labour and in all but two studies all measurements were performed after 36 weeks [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this information identifying an isolated nuchal cord antenatally is unlikely to prevent adverse outcome, but may increase intervention. However, combining identification of nuchal cord and abnormal umbilical artery flow increases the likelihood of intrapartum compromise [ 7 , 59 ]. Further test-accuracy studies are needed, but must be appropriately blinded to prevent intervention altering the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of embryos during normal pregnancy, placental trophoblast cells infiltrate continuously, UtA vascular remodelling is strengthened, the lumen is continuously enlarged, and the elasticity of the vascular wall is reduced. Uterine blood flow changes to low resistance and high flow rate from the high resistance and low flow rate before pregnancy [ 28 30 ]. The placental trophoblasts of pregnant women with HDCP have insufficient ability to infiltrate the arteries, the strength and quantity of vascular remodelling are also insufficient, the muscle layer of the vascular wall still maintains a large elasticity, and the vascular resistance goes up.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies evaluated the UA,10–29 and seven reported its predictive values for FGR. The PPV for FGR reported in the individual studies were between 77.40 and 88.5,11 16 21 24 while the area under the receiver operating characteristic (AU ROC) curve was 0.63,17 mostly in high-risk pregnancies.…”
Section: Resultsmentioning
confidence: 99%